Spatial Characterization of Bioenergetics and Metabolism of Primordial to Preovulatory Follicles in Whole Ex Vivo Murine Ovary. Issue 6 (1st December 2016) - Cinco, Rachel; Digman, Michelle A.; Gratton, Enrico; Luderer, Ulrike
Abstract: Previous work characterizing ovarian bioenergetics has defined follicular metabolism by measuring metabolic by-products in culture media. However, culture conditions perturb the native state of the follicle, and these methods do not distinguish between metabolism occurring within oocytes or granulosa cells. We applied the phasor approach to fluorescence lifetime imaging microscopy (phasor FLIM) at 740-nm two-photon excitation to examine the spatial distribution of free and protein-bound nicotinamide adenine dinucleotide hydride (NADH) during primordial through preovulatory stages of follicular development in fresh ex vivo murine neonatal and gonadotropin stimulated prepubertal ovaries. We obtained subcellular resolution phasor FLIM images of primordial through primary follicles and quantified the free/bound NADH ratio (relative NADH/NAD+) separately for oocyte nucleus and oocyte cytoplasm. We found that dynamic changes in oocyte nucleus free/bound NADH paralleled the developmental maturation of primordial to primary follicles. Immunohistochemistry of NAD+-dependent deacetylase SIRTUIN 1 (SIRT1) in neonatal ovary revealed that increasing SIRT1 expression in oocyte nuclei was inversely related to decreasing free/bound NADH during the primordial to primary follicle transition. We characterized oocyte metabolism at these early stages to be NADH producing (glycolysis/Krebs). We extended the results of prior studies to show that cumulus and mural granulosa cell metabolism in secondary through preovulatory follicles is mainly NADH producing (glycolysis/Krebs cycle), while oocyte metabolism is mainly NADH consuming (oxidative phosphorylation). Taken together, our data characterize dynamic changes in free/bound NADH and SIRT1 expression during early follicular development and confirm results from previous studies defining antral and preovulatory follicle metabolism in culture.